Procedural Flaws of Shareholders’ Resolutions – a Comparative Approach - Uliasz, Roman (Review of European and Comparative Law, 2022)
The paper discusses legal consequences of violations of law which may occur in the course of passing resolutions by shareholders or when convening the meeting. Such violations take the form of procedural infringements, as opposed to material defects which concern the subject matter of the resolution. Several jurisdictions were taken into account in order to demonstrate that illegality of the procedure does not need to imply nullity of resolutions. There are various instruments which, despite illegality, are intended to preserve the resolution. This is all about the balance of preferences: in company law there are definitely situations where legality should be less valued than stability and certainty.